Ethical Attitudes by Students - Barizsné Hadházi, Edit; Kiss, Zsuzsanna (International Journal of Engineering and Management Sciences, 2016)
We can read about empirical researches in connection with ethical behavior or attitudes by business students only in few inland but much more foreign papers. These studies examine: which behaviors are ethical or unethical by students and how strictare students in evaluation of situations. This paper aims to explore the attitudes of business students at the University of Debrecen: what they-as future organizational leaders-think about morality of a work situation.